Alcohol septal ablation in patients with concomitant hypertrophic cardiomyopathy and aortic valvular stenosis. Issue 4 (13th August 2019) - El‐Sabawi, Bassim; Nishimura, Rick A.; Guerrero, Mayra E.; Rihal, Charanjit S.; Eleid, Mackram F.
Abstract: Objective: To describe the hemodynamic and early clinical outcomes of percutaneous alcohol septal ablation in patients with concomitant dynamic left ventricular outflow tract (LVOT) obstruction and aortic valvular stenosis (AS). Background: Alcohol septal ablation is an established method to relieve dynamic LVOT obstruction in patients with hypertrophic cardiomyopathy (HCM). However, the feasibility, safety, and efficacy of alcohol septal ablation in patients with serial obstructions from HCM and AS remain unclear. Methods: In this case series, we describe the early outcomes of alcohol septal ablation in six patients with significant dynamic LVOT obstruction and AS. All patients had evidence of severe dynamic LVOT obstruction (resting or provoked gradient ≥50 mmHg), mild to severe AS, and NYHA class III symptoms or greater. Results: Four (66.7%) patients had septal ablation performed in the setting of concomitant native valvular AS and two (33.3%) patients had TAVR performed prior to septal ablation. Successful alcohol septal ablation was performed in all patients and was associated with an immediate reduction of the dynamic LVOT gradient with a residual fixed obstruction related to AS. Four (66.7%) patients had follow‐up at 1 month and of these, three (75%) had NYHA Class I–II symptoms and one (25%) Class III. Conclusions: Alcohol septal ablation is a feasible method of relieving dynamic LVOT obstruction in patients with concomitant HCM and AS. Further study is required to determine the optimal treatment approach in these patients.